'Don't send your sick here to be treated, our own people need it more': immigrants' access to health care in South Africa - Alfaro-Velcamp, Theresa (Department of Public Law, 2015)
This minor dissertation argues that there is more than a disjuncture between theory and practices, particularly for refugees and migrants and doctors in South Africa. The core idea of the Bill of Rights is that socio-economic rights are for everyone. Yet, its application suggests everyone means all citizens in the post-apartheid period, rather than all residents in South Africa. In the international domain, the human rights discourse calls on states to recognise responsibility extending to all peoples residing in a sovereign nation- state; but progressive realisation can hamper this aspiration. By employing progressive realisation within South African law, the idea that the state pays for what it can and makes future efforts to change, socio-economic rights for everyone currently cannot be achieved. This dissertation examines how Constitutional Court rulings on access to healthcare and relevant statutes have not been uniformly granted to everyone causing a disjuncture between law and practice.